(untitled) (Raparin Journal of Humanities (RJH), 2024)
Family, as a small effective system for the establishment of the entire society always leaves heated questions to scholars and social workers. Throughout the research, the issues of parental alienation have been apparently highlighted. The reasons for the foremost problems are numerous incompatibilities among the couples and the raise of many divorces. Family, as a small corporation contains several other correlations like the relation between the husband and the wife, as the formation of all the other family relations. Besides, the interactive relations of the family members then the compound families are seen. Furthermore, the new mode of the formation family relations, in the terms professions, positions, age, and literacy rate change, according to the present time of the society, culture, tradition, religion and different extents.The existence and non-existence of the modern world’s reality, family relations take many questions and issues, when this reality has apparently expressed, that the initiation, formation, role and duties are constantly changing. Furthermore, in the standard of living, the family members face challenges, alternatives and determination which all leave their influence the variety of family relations. In one way or another, the influences are seen as the catalyst of the emergence of social alienation among the families.